1995
DOI: 10.1073/pnas.92.10.4572
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA entry into postmitotic nuclei of primary rat myotubes.

Abstract: These studies were initiated to elucidate the mechanism of DNA nuclear transport in mammalian cells. Biotin-or (6). However, the same techniques have not been used successfully to study pDNA nuclear transport because <1% of the cells expressed the cytoplasmically injected pDNA (7-10). The absence of expression cannot be explained by a problem with the microinjection technique, since 50-100% of the cells showed protein expression following injection of the pDNA directly into the nucleus. These results argue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
146
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(157 citation statements)
references
References 30 publications
11
146
0
Order By: Relevance
“…However, both of these promoters generate very high levels of gene expression when injected into mouse quadricep muscles that are made up of post-mitotic, terminally differentiated myotubes (10,11). Thus, these plasmids gain access to the nuclei of these cells (33). One possible explanation for this paradox is that plasmids lacking the SV40 enhancer sequences are preferentially degraded in the cytoplasm, decreasing their numbers so that any entrance into the nucleus would be undetectable.…”
Section: Discussionmentioning
confidence: 99%
“…However, both of these promoters generate very high levels of gene expression when injected into mouse quadricep muscles that are made up of post-mitotic, terminally differentiated myotubes (10,11). Thus, these plasmids gain access to the nuclei of these cells (33). One possible explanation for this paradox is that plasmids lacking the SV40 enhancer sequences are preferentially degraded in the cytoplasm, decreasing their numbers so that any entrance into the nucleus would be undetectable.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that inefficient nuclear delivery processes independent of the cell cycle exist which facilitate transfection in cell cycle arrested cells. Indeed, Dowty et al 27 have shown that plasmid DNA microinjected into the cytosol of post-mitotic rat myotubules was capable of yielding transgene expression. From their studies, cell-cycle independent nuclear delivery of plasmid DNA clearly exists in certain cell types.…”
Section: Figure 7 Semliki Forest Virus-mediated-gene Expression Sk-omentioning
confidence: 99%
“…We, and others, have subsequently shown that nuclear import of plasmid DNA is sequence dependent, requires karyopherins (importins) and the small GTPase RAN, and occurs through the nuclear pore complex (NPC). [14][15][16][17][18] In our model of plasmid nuclear import, we propose that transcription factors present in the cytoplasm bind to the DTS and coat the plasmid with nuclear localization sequences (NLSs) that utilize importins to cross the NPC, which regulates the nucleocytoplasmic shuttling of macromolecules during interphase. [19][20][21] We have also developed a tissue-specific DTS, utilizing the smooth muscle g-actin (SMGA) promoter, that mediates nuclear import of pDNA specifically in smooth muscle cells (SMCs).…”
Section: Introductionmentioning
confidence: 99%